THE EFFECT OF THE STEAM APPROACH ON THE OUTCOMES OF SCIENCE LEARNING ON THE MATERIAL OF HUMAN RESPIRATION IN GRADE V OF SDN 11 PEMULUTAN - Sindirella, Sindirella; Lia, Linda; Fitri, Elsi Adelia (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study was conducted to determine the impact of implementing the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on the learning outcomes of fifth-grade students at SD Negeri 11 Pemulutan regarding the topic of the human respiratory system. Using an experimental method with a one-group pretest-posttest (pre-experimental) design, this study involved all fifth-grade students as research subjects. Data were collected through tests administered before and after the intervention to measure students’ academic progress. The results of the analysis showed a massive increase in learning outcomes, as evidenced by a rise in the average score from 50,3 on the pretest to 87,6 on the posttest. Using a Paired Sample T-Test, a significance value of 0.000 (p < 0.05) was obtained, meaning that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it was concluded that the STEAM method is significantly effective in boosting learning outcomes in Integrated Science (IPAS), particularly on the topic of the human respiratory system at this school.